Lipid imbalance and inflammatory oxylipin cascade at the maternal-fetal interface in recurrent spontaneous abortion - Hao Liu; Huijia Chen; Ting Han; Xin Wang; Jingcong Dai; Xiaojia Yang; ShanAn Chan; Richard D. Cannon; Yang Yang; Hatem Mousa; Shufang Chang; Ruiqi Chang; et al. (Heliyon)
Background: Recurrent spontaneous abortion (RSA) is intricately linked to metabolic dysregulation at the maternal-fetal interface during early gestation. Abnormal levels of essential fatty acids and downstream oxylipins in decidua and chorionic villi have been identified as potential risk factors for RSA. Oxylipins have been linked to excessive inflammation, which might disrupt maternal-fetal immune tolerance, potentially contributing to RSA. Nonetheless, the exact fatty acid-oxylipin metabolic pathway at the matrernal-fetal interface in RSA occurrence remains unknown. Therefore, this research aimed to explore the effect of essential fatty acids, their transport, and downstream oxylipins at the maternal-fetal interface on RSA pathogenesis. Methods: Plasma, chorionic villus, and decidual tissue samples from the first trimester were collected from healthy pregnant women undergoing elective pregnancy terminations, as well as from patients experiencing spontaneous abortion. The concentrations of essential fatty acids and their downstream oxylipins in the villi and decidua were quantified using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS). The expression of enzymes related to metabolic pathways was investigated by q-PCR. The ratios of M1/M2 macrophages were assessed by flow cytometry (FCM). Results: This study found elevated concentrations of omega-6 fatty acids, encompassing arachidonic acid (AA), linoleic acid (LA), and dihomo-gamma-linolenic acid (DGLA) in maternal plasma and chorionic villi, whereas lower concentrations were observed in the decidua, than in samples from normal pregnancies. Further analysis revealed that the transport of these fatty acids was dysregulated at the maternal-fetal interface in RSA women, possibly due to the aberrant expression of the fatty acid translocase (FAT/CD36). In addition, this study revealed that RSA patients displayed higher levels of downstream oxylipins, such as prostaglandin F2a (PGF2a), prostaglandin E2 (PGE2), and leukotriene B4 (LTB4) in chorionic villi and decidua. These compounds may contribute to M1 inflammatory macrophage polarization in RSA, thereby forming a highly inflammatory environment and influencing immunomodulation at the maternal-fetal interface. Conclusion: The study revealed alterations in omega-6 fatty acids, CD36 transport, and AA downstream oxylipins in RSA, which in turn promote M1 macrophage polarization. Thus, this research has established a foundation for identifying potential biomarkers for, and providing novel insights into, the diagnosis and pathophysiology of RSA.